Factors contributes to spontaneous abortion caused by Listeria monocytogenes, in Tehran, Iran, 2015 - Pourkaveh, B; Ahmadi, M; Eslami, G; Gachkar, L (Cellular and Molecular Biology, 2016)
Spontaneous abortion is the loss of a fetus before the 20th week of pregnancy, when occurring naturally without any surgical or pharmaceutical intervention. On the other hand, Listeria monocytogenes, as one of the foodborne pathogens, is a causative agent of listeriosis. The transfer of L. monocytogenes in pregnant women occurs as self-limited flu-like symptoms which may result in abortion, stillbirth or premature birth of infected infants. The purpose of this study was the identification of Listeria monocytogenes risk factors in women with spontaneous abortion admitted to Tehran Province health care centers in 2015. In this cross-sectional study, 317 women were examined for L. monocytogenes using Polymerase Chain Reaction (PCR) and the related risk factors. Two questionnaires on "L. monocytogenes Probable Risk Factors" and "Socio Economic Factors" were completed. Out of 317 samples of vaginal swabs, 54 (17%) isolates of L. monocytogenes were identified. In addition significant differences in terms of age of mother and her husband, mother and the husband’s level of education , house prices, place of residence, gestational age of first abortion, gestational age of current abortion, gestational age of second abortion, consumption of unpasteurized dairy products, consumption of feta and soft cheese, consumption of smoked see food products, consumption of processed meat products and half-cooked meat products, consumption of ready-to-eat vegetables, history of contact with domestic animals three month before pregnancy and during pregnancy and consumption of smoked meat products during pregnancy were studied between two groups of patients positive and negative with L. monocytogens (P < 0.001). Based on the study, the detection of L. monocytogens risk factor during pregnancy as well as taking the issue into account while giving information and counseling in pregnancy can be vital to reduce the incidence of this bacterium and subsequently its side effects during pregnancy.